Factors Affecting the Effectiveness of Contractors’ All Risk Insurance Claims: A Study of State-Owned Contractors in Indonesia - Praja, Wisnu Kurnia (Green Publisher Indonesia, 2023)
Risk affects the productivity, performance, quality, and cost constraints of construction projects; such risk can be managed by transferring it to contractors’ all risk (CAR) insurance claims. While several studies have attempted to determine the efficiency of CAR insurance in construction projects, the phenomenon model needs to be more comprehensively developed to provide contractors with strategic steps that can enhance the effectiveness of using CAR insurance to manage risk. Accordingly, this study used partial least squares structural equation modelling to overcome the shortcomings of the previous approaches used. It analyzed 33 claims data from 25 construction projects and compiled five internal/external factors: knowledge and experience of claims and the supporting role of contractor organizations (internal), and insurers, brokers, and insurance products (external). The analysis results found that the knowledge and experience of claims and insurance product factors had the most influence on claim success (β = 0.419 and 0.371, respectively). Interestingly, these factors were significantly influenced by roles and supporting organizations (β = 0.478 and 0.791, respectively). Overall, synchronizing purchased insurance policies with risk registers can increase insurance effectiveness. The findings extend the efforts to optimize the use of CAR insurance in construction projects for contractors.